APPROACH TO RISK ANALYSIS TRAWLER (BOAT OR VESSEL SIENE NETS) NORTH COAST OF EAST JAVA - Lelono, Tri Djoko; Bintoro, Gatut (JFMR (Journal of Fisheries and Marine Research), 2019)
General Linear Model (GLM) aims to find the relationship between several independent variables with one dependent variable. GLM was conducted to answer the research objectives (1) the contribution of fishing gear to the total catch of pelagic fish, (2) to determine the type of pelagic fish that was dominantly caught in the type of fishing gear based on the 2004 - 2016 East Java marine and fisheries statistical report. The results of the GLM WPP Republic of Indonesia analysis of 573, the dominant small pelagic fish were lemuru fish on payang fishing gear, selar fish in purse seine, layur fish on drifting gill nets, and bloating on fixed gill nets. While contributions based on small pelagic fishing gear are ring trawlers catching flying fish, selar fish, and anchovy. The gill nets keep catching fish, mullet, tembang fish, and mackerel. Payang catches lemuru and layur fish. Region WPP RI 712 as a result of analysis of small pelagic GLM fish: pompano fish catching equipment, anchovy with dogol fishing gear, layur fish with trawl fishing gear, gill drift fishing gear and fishing gear step, tembang fishing purse seine and tremmel net, mullet fish with fixed gill nets. Contributions based on small pelagic fishing gear are circular gill nets contributing to kite and anchovy, gill net fishing gear drifting on stingrays and layur fish, Tremmel net in Pompano fish. dogol fishing gear on mullet and mackerel, fishing gear step on tembang fish and lemuru fish. While large pelagic fish: clitic fishing gear contributes to mackerel and skipjack fish while dogol catches on tunaÂ